ZIF-8-based super-hydrophobic MOF as well as preparation method and application thereof

By modifying ZIF-8 with mixed ligands and fluorine-containing agents, the material achieves enhanced stability and hydrophobicity, effectively addressing the limitations of existing ZIF-8 materials in acidic environments for oil-water separation.

CN119241860AActive Publication Date: 2025-01-03UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411422592.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

Existing ZIF-8 materials exhibit poor stability and hydrophobic properties in acidic environments, limiting their effectiveness in complex oil-water separation systems.

Method used

A ZIF-8-based super-hydrophobic MOF is prepared using mixed ligands of 2-methylimidazole and fluorine-containing ligands, modified with alkyl acyl chloride or fluorine-containing anhydrides under the action of acid-binding agents, enhancing chemical stability and hydrophobicity.

Benefits of technology

The modified ZIF-8-based MOF demonstrates high chemical stability and excellent hydrophobic properties in acidic conditions, achieving efficient and selective oil-water separation in complex systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241860A_ABST
    Figure CN119241860A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal organic framework functional materials, and discloses a ZIF-8-based super-hydrophobic MOF as well as a preparation method and application thereof. The preparation method of the ZIF-8-based super-hydrophobic MOF comprises the following steps: taking 2-methylimidazole and a fluorine-containing ligand FL as a mixed ligand, and carrying out coordination reaction on the mixed ligand and Zn ions to obtain a ZIF-8-FL material; the preparation method comprises the following steps: carrying out grafting modification on a ZIF-8-FL material and a modifier under the action of an acid-binding agent, so as to obtain the ZIF-8-based super-hydrophobic MOF; wherein the modifier is alkyl acyl chloride or fluorine-containing anhydride. The ZIF-8-based super-hydrophobic MOF is prepared by introducing the mixed ligand and grafting modification, the process is simple, the cost is low, and the method is suitable for large-scale production; the ZIF-8-based super-hydrophobic MOF prepared by the invention has high chemical stability and excellent hydrophobic performance in an acid environment, and the defect that a conventional MOFs material is easy to degrade is avoided; the oil-water separator has excellent separation efficiency and selectivity in the oil-water separation process, can effectively separate oil-water mixtures in various complex systems, and has wide market application prospects and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal organic framework functional materials, and in particular to a ZIF-8-based super hydrophobic MOF and a preparation method and application thereof. Background Art

[0002] Oil-water separation technology is of great significance in environmental protection and industrial production, especially when dealing with complex systems such as industrial wastewater, oilfield wastewater and marine oil spills, fast and efficient oil-water separation technology is particularly important.

[0003] At present, the commonly used oil-water separation materials include membrane materials, adsorption materials and super-hydrophobic materials. However, the traditional oil-water separation materials have poor stability under acidic conditions and are easily corroded or degraded, resulting in a decrease in separation efficiency. In addition, the preparation process of some oil-water separation materials is complicated and costly, which limits their promotion in practical applications.

[0004] Metal-organic framework materials (MOFs) have attracted widespread attention in recent years due to their high specific surface area, adjustable pore size and good chemical stability. Among them, ZIF-8 is a zinc-based MOF material with a unique zeolite-like topological structure and high structural stability, showing certain application potential in the field of oil-water separation. However, the stability of existing ZIF-8 materials in acidic environments still needs to be improved, and its hydrophobic properties also need to be further enhanced to adapt to more complex oil-water separation conditions.

[0005] Based on this, it is particularly necessary to develop a ZIF-8-based metal-organic framework material with excellent stability and hydrophobic properties under acidic conditions. Summary of the invention

[0006] The present application provides a ZIF-8-based super-hydrophobic MOF and a preparation method and application thereof, aiming to solve the problems of low stability and poor hydrophobic performance of existing ZIF-8 materials in acidic environments.

[0007] In order to achieve the above objectives, the present application adopts the following technical solutions.

[0008] In a first aspect of the present application, a ZIF-8-based super-hydrophobic MOF is provided, which is prepared by the following method:

[0009] 2-Methylimidazole and fluorine-containing ligand FL were used as mixed ligands to coordinate with Zn ions to obtain ZIF-8-FL material.

[0010] The ZIF-8-FL material is grafted with a modifier under the action of an acid-binding agent to obtain;

[0011] Wherein, the modifying agent is an alkyl acyl chloride or a fluorine-containing acid anhydride.

[0012] Preferably, the chemical structure of the fluorinated ligand FL is as shown in formula (1):

[0013]

[0014] Among them, R1 is R2 is

[0015] n is an integer from 0 to 10.

[0016] Preferably, the chemical structure of the alkyl acyl chloride is as shown in formula (2):

[0017]

[0018] Wherein, x is an integer from 7 to 18;

[0019] The chemical structure of the fluorinated anhydride is shown in formula (3):

[0020]

[0021] Here, y is an integer from 0 to 4.

[0022] Preferably, the acid binding agent is triethylamine or pyridine.

[0023] Preferably, the molar percentage of the fluorine-containing ligand FL in the mixed ligand is 5-20%.

[0024] The second aspect of the present application provides a method for preparing the above-mentioned ZIF-8-based super-hydrophobic MOF, comprising:

[0025] S1, dispersing zinc nitrate hexahydrate, 2-methylimidazole and a fluorine-containing ligand FL in a first organic solvent for coordination reaction, collecting a solid phase product, washing and drying it to obtain a ZIF-8-aFL material;

[0026] S2, dispersing the ZIF-8-FL material in a second organic solvent, and then adding an acid binding agent and a modifier to carry out a grafting reaction under an inert atmosphere to obtain a ZIF-8-based super-hydrophobic MOF.

[0027] Preferably, the first organic solvent is at least one of methanol or N,N-dimethylformamide;

[0028] and / or,

[0029] The second solvent is at least one of dichloromethane, chloroform or tetrahydrofuran.

[0030] Preferably, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:(5-7);

[0031] and / or,

[0032] The mass ratio of the ZIF-8-FL material to the modifier is 1:(1-36);

[0033] and / or,

[0034] The molar ratio of the acid binding agent to the modifier is (1:1) to (1000:1).

[0035] Preferably, the temperature of the coordination reaction is 20-70°C; the temperature of the grafting reaction is 20-40°C.

[0036] The third aspect of the present application provides the use of the above-mentioned ZIF-8-based super-hydrophobic MOF or the ZIF-8-based super-hydrophobic MOF prepared by the above-mentioned preparation method in oil-water separation materials.

[0037] Compared with the prior art, the beneficial effects of this application are:

[0038] The present application prepares ZIF-8-based super-hydrophobic MOF by introducing mixed ligands and grafting modification, which has a simple process, low cost and is suitable for large-scale production.

[0039] The ZIF-8-based superhydrophobic MOF prepared in this application has high chemical stability and excellent hydrophobic properties in an acidic environment, avoiding the defect of easy degradation of conventional MOFs materials; it has excellent separation efficiency and selectivity in the oil-water separation process, and can effectively separate oil-water mixtures in a variety of complex systems, and has broad market application prospects and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0041] Figure 1 XRD patterns of MOF materials and ZIF-8 prepared in Example 1;

[0042] Figure 2 The SEM spectrum of the ZIF-8-based super-hydrophobic MOF prepared in Example 1;

[0043] Figure 3 This is a contact angle test result diagram of the ZIF-8-based super-hydrophobic MOF prepared in Example 1;

[0044] Figure 4XRD pattern of the ZIF-8-based super-hydrophobic MOF prepared in Example 1 after being soaked in hydrochloric acid for 1 week;

[0045] Figure 5 XRD pattern of the ZIF-8-based superhydrophobic MOF prepared in Example 2;

[0046] Figure 6 The SEM spectrum of the ZIF-8-based superhydrophobic MOF prepared in Example 2;

[0047] Figure 7 This is a contact angle test result diagram of the ZIF-8-based super-hydrophobic MOF prepared in Example 2;

[0048] Figure 8 XRD pattern of the ZIF-8-based superhydrophobic MOF prepared in Example 2 after being soaked in hydrochloric acid for 1 week;

[0049] Fig. 9 XRD pattern of the ZIF-8-based superhydrophobic MOF prepared in Example 3;

[0050] Fig.10 The SEM spectrum of the ZIF-8-based super-hydrophobic MOF prepared in Example 3;

[0051] Fig.11 This is a contact angle test diagram of the ZIF-8-based super-hydrophobic MOF prepared in Example 3;

[0052] Fig.12 This is the XRD pattern of the ZIF-8-based superhydrophobic MOF prepared in Example 3 after being soaked in hydrochloric acid for one week. DETAILED DESCRIPTION

[0053] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0054] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.

[0055] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0056] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0057] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0058] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0059] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0060] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0061] In a first aspect, the present application provides a ZIF-8-based super-hydrophobic MOF, which is prepared by the following method:

[0062] 2-Methylimidazole and fluorine-containing ligand FL were used as mixed ligands to coordinate with Zn ions to obtain ZIF-8-FL material.

[0063] The ZIF-8-FL material is grafted with a modifier under the action of an acid binding agent to obtain a ZIF-8-based super-hydrophobic MOF, wherein the modifier is an alkyl acyl chloride or a fluorine-containing anhydride.

[0064] In the present application, the chemical structure of the fluorinated ligand FL is shown in formula (1):

[0065]

[0066] Among them, R1 is R2 is

[0067] n is an integer from 0 to 10.

[0068] In the present application, it is preferred that the molar percentage of the fluorine-containing ligand FL in the mixed ligand is 5 to 20%.

[0069] In the present application, alkyl acyl chloride or fluorinated anhydride is used as a modifier to undergo a grafting reaction with the ZIF-8-FL material to finally obtain a ZIF-8-based super-hydrophobic MOF. The chemical structure of the alkyl acyl chloride is shown in formula (2):

[0070]

[0071] Wherein, x is an integer from 7 to 18;

[0072] The chemical structure of the fluorinated anhydride is shown in (3):

[0073]

[0074] Here, y is an integer from 0 to 4.

[0075] In the present application, the acid binding agent is used to promote the grafting reaction between the alkyl acyl chloride or the fluorine-containing acid anhydride and the ZIF-8-FL material. The acid binding agent can be triethylamine or pyridine, preferably triethylamine.

[0076] This application uses a hybrid connection strategy combined with functional modification technology to prepare a new ZIF-8 material with super-hydrophobic properties, namely, ZIF-8-based super-hydrophobic MOF. ZIF-8-based super-hydrophobic MOF has high chemical stability and excellent hydrophobic properties in an acidic environment, avoiding the defect of easy degradation of conventional MOFs materials; it has excellent separation efficiency and selectivity in the oil-water separation process, and can effectively separate oil-water mixtures in a variety of complex systems.

[0077] In a second aspect, the present application provides a method for preparing the above-mentioned ZIF-8-based super-hydrophobic MOF, comprising:

[0078] S1, dispersing zinc nitrate hexahydrate, 2-methylimidazole and a fluorine-containing ligand FL in a first organic solvent for coordination reaction, collecting a solid phase product, washing and drying it to obtain a ZIF-8-FL material;

[0079] In the present application, the first solvent can be selected from methanol or N,N-dimethylformamide, or a mixture of methanol and N,N-dimethylformamide. Zinc nitrate hexahydrate, 2-methylimidazole and the fluorine-containing ligand FL undergo coordination reaction at 20-70°C in the first solvent, the reaction product is centrifuged to collect the solid phase product, the solid phase product is washed with methanol several times, and then dried at 100-110°C for 12-24h to obtain the product ZIF-8-FL material.

[0080] Specifically, in order to illustrate the molar percentage of FL ligands in the ZIF-8-FL material, the ZIF-8-FL material is recorded as ZIF-8-(a)FL, wherein a represents the molar percentage of FL in the total ligands.

[0081] In the present application, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is preferably 1:(5-7), and the molar number of the fluorinated ligand FL is preferably 5-20% of the total molar number of the fluorinated ligand FL and 2-methylimidazole.

[0082] S2, dispersing the ZIF-8-FL material in a second organic solvent, and then adding an acid binding agent and a modifier to carry out a grafting reaction under an inert atmosphere to obtain a ZIF-8-based super-hydrophobic MOF.

[0083] In the present application, the second solvent can be selected from at least one of dichloromethane, chloroform or tetrahydrofuran. In a nitrogen atmosphere, the ZIF-8-FL material and the modifier undergo a grafting reaction in a second organic solvent at 20-40°C under the action of an acid binding agent, and the reaction product is separated by high-speed centrifugation to collect the solid phase, and the solid phase is washed with methanol for multiple times, and then dried at 100-110°C for 12-24h to obtain a ZIF-8-based superhydrophobic MOF, which is recorded as ZIF-8-aFL-b, where b represents different types of modifiers.

[0084] Among them, the mass ratio of the ZIF-8-FL material to the modifier is preferably 1:(1-36), more preferably 1:(25-36); the molar ratio of the acid-binding agent to the modifier is preferably (1:1)-(1000:1). Under these conditions, a super-hydrophobic and super-oleophilic ZIF-8-based MOF can be prepared.

[0085] The present application prepares ZIF-8-based super-hydrophobic MOF by introducing mixed ligands and grafting modification, which has a simple process, low cost and is suitable for large-scale production.

[0086] The ZIF-8-based super-hydrophobic MOF prepared in this application has high chemical stability and excellent hydrophobic properties in an acidic environment. It has excellent separation efficiency and selectivity in the oil-water separation process, can be used as an oil-water separation material, or used to prepare an oil-water separation material, can effectively separate oil-water mixtures in a variety of complex systems, and has broad application prospects.

[0087] The present application is further described below by way of examples.

[0088] Comparative Example Preparation of ZIF-8

[0089] 3.9mmol of zinc nitrate hexahydrate and 27.6mmol of 2-methylimidazole were added to a mixed solution of 40mL of methanol and 40mL of N,N-dimethylformamide. The mixed solution was reacted at 30°C for 2h, and the mixture after the reaction was centrifuged at a speed of 6000rpm to collect the centrifugal precipitate; the centrifugal precipitate was washed with methanol 3 times and dried at 100°C for 12h to obtain ZIF-8 material.

[0090] Example 1

[0091] This embodiment provides a method for preparing a ZIF-8-based super-hydrophobic MOF, comprising:

[0092] Preparation of 4-(2-(trifluoromethyl)-1H-imidazole-5-yl)phenol: 20mmol of 2-(4-hydroxyphenyl)-2-oxoacetaldehyde, 20mmol of 2,2,2-trifluoroacetaldehyde, 42mmol of ammonia water and 200mL of ethanol were mixed and stirred at 60°C for 20 hours; after cooling to room temperature, the reaction mixture was concentrated in vacuo to remove ethanol; 50mL of water was added to the concentrate, extracted with ethyl acetate (3×20mL), and then the extract was dried over anhydrous magnesium sulfate, filtered and concentrated in vacuo; the residue was sublimed to obtain a solid. Among them, the chemical structure of 4-(2-(trifluoromethyl)-1H-imidazole-5-yl)phenol is shown below:

[0093]

[0094] S1, 3.9mmol of zinc nitrate hexahydrate, 22.08mmol of 2-methylimidazole and 5.52mmol of 4-(2-(trifluoromethyl)-1H-imidazole-5-yl)phenol were added to a mixed solution of 40mL of methanol and 40mL of N,N-dimethylformamide, wherein the molar percentage of 4-(2-(trifluoromethyl)-1H-imidazole-5-yl)phenol in the mixed ligand was 20%. The mixed solution was reacted at 30°C for 2h, and the mixture after the reaction was centrifuged at a speed of 6000rpm to collect the centrifugal precipitate; the centrifugal precipitate was washed with methanol 3 times and dried at 100°C for 12h to obtain a ZIF-8-FL material, which was recorded as ZIF-8-20%FL.

[0095] S2, 0.03 g of ZIF-8-20% FL was ultrasonically dispersed in 15 mL of chloroform, and then 348 μl of triethylamine and 612 μl of heptafluorobutyric anhydride were added under nitrogen atmosphere, and stirred at 30°C for 24 h. The reaction mixture was centrifuged at 6000 rpm to collect the centrifugal precipitate; the centrifugal precipitate was washed with methanol three times and dried at 100°C for 12 h to obtain a ZIF-8-based superhydrophobic MOF, recorded as ZIF-8-20% FL-7F.

[0096] The MOF material prepared in Example 1 and the ZIF-8 material of the comparative example were characterized. The XRD spectra of ZIF-8-20% FL and ZIF-8-20% FL-7F prepared in Example 1 and ZIF-8 prepared in the comparative example are as follows: Figure 1 As shown. Figure 1 It can be seen that ZIF-8-20% FL, ZIF-8-20% FL-7F and ZIF-8 show the same peaks at the corresponding positions, that is, the skeleton structure and crystallinity of the ZIF-8 structure are retained in the complex ZIF-8-20% FL and the ZIF-8-based superhydrophobic MOF ZIF-8-20% FL-7F prepared in this application.

[0097] The ZIF-8-based super-hydrophobic MOF prepared in Example 1, namely ZIF-8-20% FL-7F, was subjected to morphological characterization test. Figure 2 As shown. Figure 2 It can be seen that the morphology of the ZIF-8-20% FL-7F sample shows a typical rhombic dodecahedron morphology. Compared with the particle size of ZIF-8 nanocrystals (about 50 nm), the average particle size of ZIF-8-20% FL-7F crystals increased by 10 times to 500 nm.

[0098] The hydrophobicity test of ZIF-8-20% FL-7F prepared in Example 1 was carried out, and the contact angle test results are as follows: Figure 3 As shown. Figure 3 It can be seen that the contact angle of ZIF-8-20% FL-7F with water is 151.9°, indicating that ZIF-8-20% FL has excellent superhydrophobicity.

[0099] The stability test of ZIF-8-20% FL-7F prepared in Example 1 was carried out as follows:

[0100] It was immersed in a hydrochloric acid solution with a pH of 2 for 1 week, and then its XRD spectrum was tested. The test results are as follows: Figure 4 As shown. Figure 4 It can be seen that after being immersed in a hydrochloric acid solution with a pH of 2 for one week, ZIF-8-20% FL-7F still maintains a typical ZIF-8 diffraction structure, and its framework structure remains relatively intact under acidic conditions, with high stability.

[0101] Example 2

[0102] This embodiment provides a method for preparing a ZIF-8-based super-hydrophobic MOF, comprising:

[0103] Preparation of 4-(5-(trifluoromethyl)-1H-1,2,4-triazol-3-yl)phenol: 20mmol of ethyl trifluoroacetate, 26mmol of 85% hydrazine hydrate and 200mL of ethanol were mixed and stirred at 67°C for 2 hours. After cooling to room temperature, 16mmol of 4-hydroxybenzamidine hydrochloride and 16mmol of potassium hydroxide were added, and refluxed and stirred for 20 hours; after cooling to room temperature, the reaction mixture was concentrated in vacuo to remove ethanol; 50mL of water was added to the concentrate, extracted with ethyl acetate (3×20mL), dried over anhydrous magnesium sulfate, filtered, and concentrated in vacuo. The residue was sublimed to obtain a solid. Among them, the chemical structure of 4-(5-(trifluoromethyl)-1H-1,2,4-triazol-3-yl)phenol is shown below:

[0104]

[0105] S1, 3.9mmol of zinc nitrate hexahydrate, 22.63mmol of 2-methylimidazole and 4.97mmol of 4-(5-(trifluoromethyl)-1H-1,2,4-triazol-3-yl)phenol were added to a mixed solution of 40mL of methanol and 40mL of N,N-dimethylformamide, wherein the molar percentage of 4-(2-(trifluoromethyl)-1H-imidazole-5-yl)phenol in the mixed ligand was 18%. The mixed solution was reacted at 30°C for 2h, and the mixture after the reaction was centrifuged at a speed of 6000rpm to collect the centrifugal precipitate; the centrifugal precipitate was washed with methanol 3 times and dried at 100°C for 12h to obtain a ZIF-8-FL material, which was recorded as ZIF-8-18%FL.

[0106] S2, 0.03 g of ZIF-8-18% FL was ultrasonically dispersed in 15 mL of chloroform, and then 348 μl of triethylamine and 0.76 g of octadecyl chloride were added under nitrogen atmosphere, and the mixture was stirred at 30°C for 24 h. The reaction mixture was centrifuged at 6000 rpm to collect the centrifugal precipitate; the centrifugal precipitate was washed with methanol 3 times and dried at 100°C for 12 h to obtain a ZIF-8-based superhydrophobic MOF, which was recorded as ZIF-8-18% FL-C18.

[0107] The XRD pattern of ZIF-8-18% FL-C18 prepared in Example 2 is as follows Figure 5 As shown. Figure 5 It can be seen that relative to IF-8, ZIF-8-18% FL-C18 also exhibits the same peaks at the corresponding positions, which retains the skeleton structure and crystallinity of the ZIF-8 structure.

[0108] The ZIF-8-18% FL-C18 prepared in Example 2 was subjected to morphological characterization test, and its SEM was as follows: Figure 6 As shown. Figure 6 It can be seen that the morphology of the ZIF-8-18% FL-C18 sample shows a typical rhombic dodecahedron morphology, but compared with the particle size of ZIF-8 nanocrystals (about 50 nm), the average particle size of ZIF-8-18% FL-C18 crystals increased by 8 times to 400 nm.

[0109] The hydrophobicity test of ZIF-8-18% FL-C18 prepared in Example 2 was carried out, and the contact angle test results are as follows: Figure 7 As shown. Figure 7 It can be seen that the contact angle of ZIF-8-18% FL-C18 with water is 152.1°, indicating that ZIF-8-18% FL-C18 has excellent superhydrophobicity.

[0110] The stability of ZIF-8-18% FL-C18 prepared in Example 2 was tested by soaking it in a hydrochloric acid solution with a pH of 2 for 1 week and then testing its XRD spectrum. The test results are shown in FIG. Figure 8 As shown. Figure 8 It can be seen that after being immersed in a hydrochloric acid solution with a pH of 2 for one week, ZIF-8-18% FL-C18 still maintains the typical ZIF-8 diffraction structure, and its framework structure remains relatively intact under acidic conditions, with high stability.

[0111] Example 3

[0112] This embodiment provides a method for preparing a ZIF-8-based super-hydrophobic MOF, comprising:

[0113] Preparation of 4-(5-(trifluoromethyl)-1H-1,2,4-triazol-3-yl)butan-1-ol: 20 mmol of ethyl trifluoroacetate, 26 mmol of 85% hydrazine hydrate and 200 mL of ethanol were mixed and stirred at 67°C for 2 hours; after cooling to room temperature, 16 mmol of 5-hydroxypentanimide hydrochloride and 16 mmol of potassium hydroxide were added, and the mixture was refluxed and stirred for 20 hours; after cooling to room temperature, the reaction mixture was concentrated in vacuo to remove ethanol; 50 mL of water was added to the concentrate, extracted with ethyl acetate (3×20 mL), dried with anhydrous magnesium sulfate, filtered, and concentrated in vacuo; the residue was sublimed to obtain a solid. Among them, the chemical structure of 4-(5-(trifluoromethyl)-1H-1,2,4-triazol-3-yl)butan-1-ol is shown below:

[0114]

[0115] S1, 3.9mmol of zinc nitrate hexahydrate, 23.46mmol of 2-methylimidazole and 4.14mmol of 4-(5-(trifluoromethyl)-1H-1,2,4-triazol-3-yl)butan-1-ol were added to a mixed solution of 40mL of methanol and 40mL of N,N-dimethylformamide, wherein the molar percentage of 4-(2-(trifluoromethyl)-1H-imidazole-5-yl)phenol in the mixed ligand was 15%. The mixed solution was reacted at 30°C for 2h, and the mixture after the reaction was centrifuged at a speed of 6000rpm to collect the centrifugal precipitate; the centrifugal precipitate was washed with methanol 3 times and dried at 100°C for 12h to obtain a ZIF-8-FL material, which was recorded as ZIF-8-15%FL.

[0116] S2, 0.03 g of ZIF-8-15% FL was ultrasonically dispersed in 15 mL of chloroform, and then 348 μl of triethylamine and 493 μl of pentafluoropropionic anhydride were added under nitrogen atmosphere, and stirred at 30°C for 24 h. The reaction mixture was centrifuged at 6000 rpm to collect the centrifugal precipitate; the centrifugal precipitate was washed with methanol 3 times and dried at 100°C for 12 h to obtain a ZIF-8-based superhydrophobic MOF, recorded as ZIF-8-15% FL-5F.

[0117] The XRD pattern of ZIF-8-15% FL-5F prepared in Example 3 is as follows: Fig. 9 As shown. Fig. 9 It can be seen that relative to ZIF-8, ZIF-8-15% FL-5F also exhibits the same peak at the corresponding position, which retains the skeleton structure and crystallinity of the ZIF-8 structure.

[0118] The ZIF-8-15% FL-5F prepared in Example 3 was subjected to morphological characterization test, and its SEM was as follows: Fig.10As shown. Fig.10 It can be seen that the morphology of the ZIF-8-15% FL-5F sample shows a typical rhombic dodecahedron morphology. Compared with the particle size of ZIF-8 nanocrystals (about 50 nm), the average particle size of ZIF-8-15% FL-5F crystals increased by 4 times to 200 nm.

[0119] The hydrophobicity test of ZIF-8-15% FL-5F prepared in Example 3 was carried out, and the contact angle test results are as follows: Fig.11 As shown. Fig.11 It can be seen that the contact angle of ZIF-8-15% FL-5F with water is 155.7°, indicating that ZIF-8-15% FL-5F has excellent superhydrophobicity.

[0120] The stability of ZIF-8-15% FL-5F prepared in Example 3 was tested by soaking it in a hydrochloric acid solution with a pH of 2 for 1 week and then testing its XRD spectrum. The test results are shown in FIG. Fig.12 As shown. Fig.12 It can be seen that after being immersed in a hydrochloric acid solution with a pH of 2 for one week, ZIF-8-15% FL-5F still maintains a typical ZIF-8 diffraction structure, and its framework structure remains relatively intact under acidic conditions, with high stability.

[0121] The ZIF-8-based super-hydrophobic MOF prepared in Examples 1-3 were used to prepare ZIF-8-based super-hydrophobic MOF@PP composite membranes, and oil-water separation experiments were performed to test their oil-water separation performance. The method is as follows:

[0122] 20 mg of ZIF-8-based superhydrophobic MOF and 2 mg of polyvinylidene fluoride were dispersed in N-methyl-2-pyrrolidone, respectively. The slurry was stirred for 1 hour and then coated on one side of PP with a spatula. It was then vacuum dried at 60 °C for 12 hours to prepare ZIF-8-20% FL-7F@PP composite membrane, ZIF-8-18% FL-C18@PP composite membrane and ZIF-8-15% FL-5F@PP composite membrane.

[0123] 100g toluene, 0.1g sodium dodecyl sulfate and 10g hydrochloric acid (pH=2) were mixed evenly and stirred at 700rpm for 24 hours to prepare an oil-in-water emulsion. A filtration system was assembled with a hole and a filtration bottle, and the above three composite membranes were cut into discs with a diameter of about 4cm, which were used as filter membranes to separate oil and water from emulsified oil wastewater.

[0124] In order to quantitatively evaluate the separation precision, the separation efficiency was calculated by testing the retention rate (Rj):

[0125] Rj=(1-C p / C f)×100%

[0126] Cp and Cf represent the water concentration in the permeate and feed solution, respectively.

[0127] After testing, the composite membrane containing the ZIF-8-based superhydrophobic MOF prepared in this application has an excellent separation effect on oil-water mixtures. Among them, the ZIF-8-20% FL-7F@PP composite membrane separates a toluene-hydrochloric acid mixed solution with a pH of 2, and the separation efficiency reaches 98.4%. The ZIF-8-18% FL-C18@PP composite membrane separates a toluene-hydrochloric acid mixed solution with a pH of 2, and the separation efficiency reaches 98.7%. The ZIF-8-15% FL-5F@PP composite membrane separates a toluene-hydrochloric acid mixed solution with a pH of 2, and the separation efficiency reaches 99.3%.

[0128] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.

Claims

1. A ZIF-8-based super-hydrophobic MOF, characterized in that: Prepared by the following method: 2-Methylimidazole and fluorine-containing ligand FL were used as mixed ligands to coordinate with Zn ions to obtain ZIF-8-FL material. The ZIF-8-FL material is grafted with a modifier under the action of an acid-binding agent to obtain a ZIF-8-based superhydrophobic MOF; Wherein, the modifying agent is an alkyl acid chloride or a fluorine-containing acid anhydride.

2. The ZIF-8 based super hydrophobic MOF according to claim 1, characterized in that The chemical structure of the fluorinated ligand FL is shown in formula (1): Among them, R1 is R2 is n is an integer from 0 to 10.

3. The ZIF-8 based super hydrophobic MOF according to claim 1, characterized in that The chemical structure of the alkyl acyl chloride is shown in formula (2): Wherein, x is an integer from 7 to 18; The chemical structure of the fluorinated anhydride is shown in formula (3): Here, y is an integer from 0 to 4.

4. The ZIF-8 based super hydrophobic MOF according to claim 1, characterized in that The acid binding agent is triethylamine or pyridine.

5. The ZIF-8 based super hydrophobic MOF according to claim 1, characterized in that The molar percentage of the fluorine-containing ligand FL in the mixed ligand is 5-20%.

6. The method for preparing the ZIF-8-based super-hydrophobic MOF according to claim 1, characterized in that: include: S1, dispersing zinc nitrate hexahydrate, 2-methylimidazole and a fluorine-containing ligand FL in a first organic solvent for coordination reaction, collecting a solid phase product, washing and drying it to obtain a ZIF-8-FL material; S2, dispersing the ZIF-8-FL material in a second organic solvent, and then adding an acid binding agent and a modifier to carry out a grafting reaction under an inert atmosphere to obtain a ZIF-8-based super-hydrophobic MOF.

7. The preparation method according to claim 6, characterized in that: The first organic solvent is at least one of methanol or N,N-dimethylformamide; and / or, The second solvent is at least one of dichloromethane, chloroform or tetrahydrofuran.

8. The preparation method according to claim 6, characterized in that: The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:(5-7); and / or, The mass ratio of the ZIF-8-FL material to the modifier is 1:(1-36); and / or, The molar ratio of the acid binding agent to the modifier is (1:1) to (1000:1).

9. The preparation method according to claim 6, characterized in that: The temperature of the coordination reaction is 20 to 70°C; The temperature of the grafting reaction is 20-40°C.

10. Use of the ZIF-8-based super-hydrophobic MOF according to any one of claims 1 to 5 or the ZIF-8-based super-hydrophobic MOF prepared by the preparation method according to any one of claims 6 to 9 in oil-water separation materials.

Citation Information

Patent Citations

  • Preparation method and application of super-hydrophobic zeolite imidazole metal-organic framework F-ZIF-90

    CN106317086A

  • Zeolite imidazate framework / polyamide composite membrane and preparation method thereof

    CN106390768A

  • Metal-organic framework material with hydrophobic surface and preparation method and applications thereof

    CN108948367A

  • Hydrophobic oleophylic polymer / MOF mixed matrix membrane as well as preparation method and application thereof

    CN113292754A

  • MOFs (Metal-Organic Frameworks) composite cotton material containing bis (trifluoromethyl) as well as preparation method and application of MOFs composite cotton material

    CN117659515A

Cited By

  • Modified diamine-modified magnesium-based MOF-loaded hydrophobic chestnut shell fiber aerogel as well as preparation method and application thereof

    CN120285963A

  • Super-hydrophobic anti-corrosion and anti-icing coating as well as preparation method and application thereof

    CN121343445A